2014
DOI: 10.1111/acps.12275
|View full text |Cite
|
Sign up to set email alerts
|

Waiting list may be a nocebo condition in psychotherapy trials: a contribution from network meta‐analysis

Abstract: There may be important differences in control conditions currently used in psychotherapy trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
271
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(291 citation statements)
references
References 70 publications
15
271
4
1
Order By: Relevance
“…However, a waiting list is a poor means of "no treatment control" because it induces a dynamic (the expectation of being treated in the near future) that differs from that in an observation study arm only (Relton et al, 2010). It has even been suggested that "waiting list" is a "nocebo" intervention, although evidence for such a worsening effect is limited to analyses that failed to take sample size into account (Furukawa et al, 2014).…”
Section: A Effect Sizes Of Symptom Improvement Across Different Medimentioning
confidence: 99%
See 1 more Smart Citation
“…However, a waiting list is a poor means of "no treatment control" because it induces a dynamic (the expectation of being treated in the near future) that differs from that in an observation study arm only (Relton et al, 2010). It has even been suggested that "waiting list" is a "nocebo" intervention, although evidence for such a worsening effect is limited to analyses that failed to take sample size into account (Furukawa et al, 2014).…”
Section: A Effect Sizes Of Symptom Improvement Across Different Medimentioning
confidence: 99%
“…Waiting controls also develop their own dynamics; on the one hand, patients may improve while waiting because of being assured of receiving active treatment soon (Beck et al, 2015), similar to the effects seen in placebo run-in phases ). On the other hand, it may be regarded as a punishment for patients not to be included in the active treatment condition (Furukawa et al, 2014). If waiting list controls are included, a "step-wedge" design may be superior, because it allows a "dose-response" assessment of waiting for treatment (Fig.…”
mentioning
confidence: 99%
“…The use of passive control conditions in trials is fraught with limitations. For example, waitlist controls have been shown to inflate treatment effect sizes in comparison to 'no treatment' control conditions, 65 and TAU conditions are often heterogeneous reducing the generalizability of findings. 66 Only one trial 62 compared CBT to another evidence-based psychotherapy (CBT versus ACT), and so future studies certainly need to use valid active controls.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Hence it remains unclear to what extent the reported effects can be attributed to specific psychotherapeutic interventions (161). Of course, control treatments such as TAU or GCC should not be equated across studies, and research suggests that the choice of comparison treatment can considerably influence effect sizes in psychotherapy research (199,200), which has also been demonstrated in recent RCTs for treatments of borderline PD in adult patients (201)(202)(203)(204)(205). However, a general finding from RCTs for treatment of borderline PD in both adolescent and adult samples (206) and in reviews and metaanalyses of psychotherapy outcome research is that there is often little or no difference in efficacy among various bona fide psychotherapeutic treatments (207)(208)(209)(210); a finding commonly referred to as the Dodo bird verdict (211).…”
Section: Taking the Dodo Bird Serious: Effective Ingredients And Commmentioning
confidence: 99%